Climate-driven spatial and temporal patterns in peatland pool biogeochemistry - Arsenault, Julien; Talbot, Julie; Brown, Lee E.; Helbig, Manuel; Holden, Joseph; Hoyos-Santillan, Jorge; Jolin, Emilie; Mackenzie, Roy; Martinez-Cruz, Karla; Sepulveda-Jauregui, Armando; Lapierre, Jean-Francois (My University, 2023)
Peatland pools are freshwater bodies that are highly dynamic aquatic ecosystems because of their small size and their development in organic-rich sediments. However, our ability to understand and predict their contribution to both local and global biogeochemical cycles under rapidly occurring environmental change is limited because the spatiotemporal drivers of their biogeochemical patterns and processes are poorly understood. We used (1) pool biogeochemical data from 20 peatlands in eastern Canada, the United Kingdom, and southern Patagonia and (2) multi-year data from an undisturbed peatland of eastern Canada, to determine how climate and terrain features drive the production, delivering and processing of carbon (C), nitrogen (N), and phosphorus (P) in peatland pools. Across sites, climate (24%) and terrain (13%) explained distinct portions of the variation in pool biogeochemistry, with climate driving spatial differences in pool dissolved organic C (DOC) concentration and aromaticity. Within the multi-year dataset, DOC, carbon dioxide (CO2), total N concentrations, and DOC aromaticity were highest in the shallowest pools and at the end of the growing seasons, and increased gradually from 2016 to 2021 in relation to a combination of increases in summer precipitation, mean air temperature for the previous fall, and number of extreme summer heat days. Given the contrasting effects of terrain and climate, broad-scale terrain characteristics may offer a baseline for the prediction of small-scale pool biogeochemistry, while broad-scale climate gradients and relatively small year-to-year variations in local climate induce a noticeable response in pool biogeochemistry. These findings emphasize the reactivity of peatland pools to both local and global environmental change and highlight their potential to act as widely distributed climate sentinels within historically relatively stable peatland ecosystems.
Keywords: biogeochemistry; carbon; climate change; climate sentinels; landscape change; nutrient cycling; ponds